Identification of the flavor profiles of Chinese pancakes from various areas using smart instruments combined with E-noses and E-tongues - Liu, Wei; Fan, Yue; Liu, Qiannan; Xu, Fen; Zhang, Liang; Hu, Honghai (International Journal of Agricultural and Biological Engineering, 2023)
In order to reveal the flavor characteristics of Chinese pancakes, the aroma and taste compounds of seven traditional Chinese pancakes were identified. The results showed that electronic nose (E-nose) analysis with PCA could successfully distinguish the aroma profiles of seven Chinese pancakes; the principal components PC1 and PC2 represented 75.74% and 23.2% of the total variance (98.94%) respectively. Meanwhile, the discrimination index of taste profiles of seven Chinese pancakes based on electronic tongue (E-tongue) analysis with LDA was 99.32%; the discriminant factors DF1 and DF2 represented 94.99% and 4.33% of the total variance respectively. Furthermore, GC-MS results demonstrated that thirty-three flavor compounds were identified in seven Chinese pancakes, including aldehydes, alcohols, alkanes, acids, and aromatics. Among the flavor components, aldehydes with ROAVs higher than 1 contributed most significantly to the overall aroma, such as (E,E)-2,4-nonadienal present the largest contribution in Qingzhou pancake, Jinan and Yishui pancake; hexanal present the largest contribution in Shenxian and Gaomi pancake; nonanal and benzeneacetaldehyde present the largest contribution in Linqu and Tai’an pancake, respectively. The umami and sweet taste amino acids were the most abundant in all the Chinese pancake samples, and Qingzhou pancake had relatively high amino acid content. The content of glucose was higher than maltose in Gaomi, Shenxian, and Tai’an pancakes, whereas the content of maltose was higher than glucose in Linqu, Qingzhou, Jinan, and Yishui pancakes. These results indicated that the aroma and taste profiles of Chinese pancakes differed significantly in terms of their flavor compound composition. The presented results could be beneficial for providing a comprehensive method for flavor profile identification of traditional whole-grain-based staples such as Chinese pancakes.Keywords: Chinese pancake, flavor profile, E-nose, E-tongue, smart instrument, identificationDOI: 10.25165/j.ijabe.20231601.6817Citation: Liu W, Fan Y, Liu Q N, Xu F, Zhang L, Hu H H. Identification of flavor profiles of Chinese pancakes from various areas using smart instruments combined with E-noses and E-tongues. Int J Agric & Biol Eng, 2023; 16(1): 283–290.